Kitab al-Muzhir of Jalal al-Din al-Suyuti: A Critical Edition and Translation of Section Twenty on Islamic Terms - Munirul Ikhwan (Al-Jami'ah: Journal of Islamic Studies, 2009)
This article is a philological study of al-Muzhir, an encyclopedic work of a prominent Egyptian scholar Jalal al-Din al-Suyuti (d. 911/1505) which has significant contribution in the study of Arabic linguistics. The book is particularly al-Suyuti's own compilation of works of earlier philologists. Due to its importance, it is necessary to study the book in a proper way by deciphering its manuscripts. Studying a book from its manuscripts provides us with much indirect information -which has great value for scholarship- to trace back the history of the book before the printing period. Apart from the text itself, manuscripts generally contain the owner's seal, introductory remark, colophon, certificate and commentaries. Through examining these additional elements, we may be able to acquire the information about the distribution and public demand of the book, the scribes and days of copying, and the authorization of its manuscripts. This paper will discuss al-Muzhir by analyzing a number of manuscripts written several decades after the death of the author. It will then focus on the authorization of the manuscripts, a sample of critical edition of the book, and a discussion of section twenty on Islamic terms.